Description in literature and other media - Wolf, Werner; Bernhart, Walter (Studies in intermediality, 2007)
In contrast to narrative, description is a much less researched phenomenon, and where it so far has found attention at all, scholars have almost always discussed it with fiction in mind. The all but exclusive concentration on literature has hitherto obscured the fact that description transcends literature and indeed the verbal media in general and is not only a transgeneric but also a transmedial phenomenon that can be found in many other media and arts. This book is a pioneering interdisciplinary study of description since it for the first time undertakes to close this research lacuna by highlighting description and its relevance with reference to a wide spectrum of arts and media. The volume opens with a detailed introductory essay, which aims at clarifying the descriptive as a basic semiotic form of organizing signs from a theoretical perspective but also provides a first overview of the uses of description as well as its problematics in fiction, painting and instrumental music. In the main part of the book, nine contributions by scholars from various disciplines explore description in individual media and different cultural epochs. The first section of the book is dedicated to literature and related (partly) verbal media and includes a typological and historical survey of description in fiction as well as discussions of its occurrence in poetry, nature writing, radioliterature and film. The second part deals with the (purely) visual media and ranges from a presentation of the descriptive techniques used in Durer?s graphic reproductions to general reflections on 'the descriptive? in the visual arts as well as in photography. A third section on description in music provides a perspective on yet another medium. The volume, which is the second one in the series 'Studies in Intermediality?, is of relevance to students and scholars from various fields: intermedial studies, literary and film studies, history of art, and musicology. ContentsPreface IntroductionWerner WOLF: Description as a Transmedial Mode of Representation: General Features and Possibilities of Realization in Painting, Fiction and Music Description in Literature and Related (Partly) Verbal MediaAnsgar NUNNING: Towards a Typology, Poetics and History of Description in FictionWalter BERNHART: Functions of Description in Poetry Arno HELLER: Description in American Nature Writing Doris MADER: The Descriptive in Audio-/Radioliterature? a 'Blind Date?? Klaus RIESER: For Your Eyes Only: Some Thoughts on the Descriptive in Film Description in Visual MediaJohann Konrad EBERLEIN: Durer?s Apocalypse as the Origin of the Western System of Graphic Reproduction: A Contribution to the History of Descriptive Techniques in the Visual Arts Gotz POCHAT: Spiritualia sub metaphoris corporalium? Description in the Visual ArtsSusanne KNALLER: Descriptive Images: Authenticity and Illusion in Early and Contemporary Photography Description in MusicMichael WALTER: Musical Sunrises: A Case Study of the Descriptive Potential of Instrumental Music Notes on Contributors.